2009
DOI: 10.1111/j.1708-8208.2009.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

The Buccofacial Wall of Maxillary Sinus: An Anatomical Consideration for Sinus Augmentation

Abstract: These observations indicate that anatomical characteristics of the buccofacial wall thickness of the maxillary sinus need to be considered when performing a window opening procedure for sinus augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
29
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 6 publications
8
29
4
1
Order By: Relevance
“…14,15 In contrast, in a study of 74 non-embalmed Korean hemifaces, Yang et al 13 reported that the buccofacial wall was thinner in the second molar region than in the first molar region, in agreement with the current findings. A similar observation was recently reported by Danesh-Sani et al 19 Surprisingly, Li et al 12 found that the buccofacial wall gradually became thinner from the region of the second premolar towards the region of the second molar, 5 mm from the floor of the sinus.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…14,15 In contrast, in a study of 74 non-embalmed Korean hemifaces, Yang et al 13 reported that the buccofacial wall was thinner in the second molar region than in the first molar region, in agreement with the current findings. A similar observation was recently reported by Danesh-Sani et al 19 Surprisingly, Li et al 12 found that the buccofacial wall gradually became thinner from the region of the second premolar towards the region of the second molar, 5 mm from the floor of the sinus.…”
Section: Discussioncontrasting
confidence: 48%
“…12,13,14,15,16,17,18,19 . Because of the different landmarks used (axis of the teeth or the interdental region versus different distances from the floor of the sinus), these studies reported vastly different findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maxillary sinus augmentation is performed by using two different surgical approaches, the lateral window approach and the crestal approach [7]. Both techniques have shown acceptable results; however, the lateral window approach is still considered more predictable in terms of outcome and safety, especially for cases with minimal bone height [8, 9].…”
Section: Introductionmentioning
confidence: 99%